2010
DOI: 10.1159/000317138
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation in Chronic Respiratory Failure: Effects on Quality of Life

Abstract: Background: Noninvasive ventilation (NIV) has been found to be an essential technique to treat chronic respiratory failure (CRF) resulting from restrictive thoracic disorders (RTD). The last decades were characterized by the expansion of NIV to treat patients suffering from various other conditions, such as chronic obstructive pulmonary disease (COPD) and obesity hypoventilation syndrome (OHS). Objectives: The aim of this study was to evaluate the effect of NIV on health-related quality of life (HRQoL) of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 73 publications
3
34
0
4
Order By: Relevance
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk There were three small prospective uncontrolled observational studies, two 106,107 in stable populations (n = 11 and n = 35) and one 108 in a post-hospital population (n = 27) (see Appendix 8 for further details). The study in a post-hospital population did not report before and after (NIV) data and so did not add useful information.…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk There were three small prospective uncontrolled observational studies, two 106,107 in stable populations (n = 11 and n = 35) and one 108 in a post-hospital population (n = 27) (see Appendix 8 for further details). The study in a post-hospital population did not report before and after (NIV) data and so did not add useful information.…”
Section: Clinical Effectiveness Review Resultsmentioning
confidence: 99%
“…Only three studies (no restriction on sample size or length of follow-up) reported exacerbations. Neither the prospective uncontrolled study by Tsolaki 107 in 2011 nor the retrospective study by Windisch 109 in 2009, both in stable populations, made a distinction between different severities of exacerbation. The report of a further small (n = 20) Japanese study 64 was not translated.…”
Section: Exacerbationsmentioning
confidence: 99%
“…It is also applied in COPD patients, although its efficacy is less well demonstrated in this disease. However, the method is inapplicable to some patients with poor mask tolerance and other well-known factors [1] . Recently, high flow rates of room air or room air/oxygen gas mixtures have been tried in situations of sleep apnea and Key Words Nasal high flow ؒ Tidal volume ؒ Hypercapnia ؒ Idiopathic pulmonary fibrosis ؒ COPD Abstract Background: A high flow of air applied by large bore nasal cannulae has been suggested to improve symptoms of chronic respiratory insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Home noninvasive ventilation (NIV) aims to improve quality of life [4], quality of sleep and survival, correct hypoventilation and associated symptoms, and daytime and nocturnal blood gases. Monitoring of the efficacy of home NIV usually relies on daytime arterial blood gases (ABGs) and nocturnal pulse oxymetry (a few centers use polysomnography for monitoring their NIV patients).…”
Section: Introductionmentioning
confidence: 99%